The needs for developing a simple financial report template to improve student understanding of simple business financial management - Sulastri, Sulastri (Research in Education and Technology (REGY), 2024)
This research aimed to describe the development of a financial report template for economics learning at SMAN 19 Tebo. This research method was carried out using non-associative quantitative analysis. The sample consisted of 32 people from a population of 48 people. Data collection techniques through observation and questionnaires. The research results from the needs analysis showed that the indicator of interest in module templates (flipbook media) was 73% which is in the medium category. Indicator perception of learning motivation was 90% which is included in the very high category. Indicator perception of learning outcomes also showed a very high figure with 93%. Indicator perception regarding the use of module templates (flipbook media) to increase students’ understanding in learning financial reports showed a high figure with 89%. This showed that developing module templates using flipbook media can improve students’ learning understanding of financial reporting material at SMAN 19 Tebo.